2022
DOI: 10.3390/metabo12090817
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Sensitivity of Multi-Distance Hyperspectral NIRS to Changes in the Oxidation State of Cytochrome C Oxidase in the Brain

Abstract: Near-infrared spectroscopy (NIRS) measurements of tissue oxygen saturation (StO2) are frequently used during vascular and cardiac surgeries as a non-invasive means of assessing brain health; however, signal contamination from extracerebral tissues remains a concern. As an alternative, hyperspectral (hs)NIRS can be used to measure changes in the oxidation state of cytochrome c oxidase (ΔoxCCO), which provides greater sensitivity to the brain given its higher mitochondrial concentration versus the scalp. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…DCS data were acquired using an in-house DCS system that included a continuous long coherence length (>10 m) emitting at 786 nm (DL852-100-SO, CrystaLaser, USA) [13]. The laser was coupled to a single fiber (core diameter 400 μm, NA = 0.22, Loptek, Germany).…”
Section: Instrumentationmentioning
confidence: 99%
“…DCS data were acquired using an in-house DCS system that included a continuous long coherence length (>10 m) emitting at 786 nm (DL852-100-SO, CrystaLaser, USA) [13]. The laser was coupled to a single fiber (core diameter 400 μm, NA = 0.22, Loptek, Germany).…”
Section: Instrumentationmentioning
confidence: 99%
“…Measurements were acquired for 8 min (baseline) before deoxygenation of the solution in the bottom compartment by 2 g of yeast dissolved in 2 mL of 50% glucose and 1 mL of SBB. No yeast was added to the top layer compartment to mimic the low mitochondrial concentration in the ECL relative to the brain 25 , 63 . The bottom layer was left to deoxygenate for 28 min before reoxygenation was initiated by bubbling oxygen gas through the air stone.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that oxCCO can be monitored in piglets and neonates using CW systems; 5 , 7 , 24 however, extending the technique to adults has been hampered by contamination of brain-related signals by the thick adult extracerebral layers (ECL; scalp and skull) 6 , 25 , 26 . In adults, substantial light absorption and scattering occur in these surface layers, limiting light penetration into deeper tissues and reducing sensitivity to the brain 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This work aimed to assess Kernel Flow's sensitivity to regional cerebral oxygenation changes using carotid compression (CC), a paradigm which results in substantial blood flow and oxyhemoglobin (HbO) reductions across the entire ipsilateral hemisphere. 6…”
Section: Introductionmentioning
confidence: 99%